Efficacy and Safety of Integrated Traditional Chinese and Western Medicine for Corona Virus Disease 2019 (COVID-19): a systematic review and meta-analysis - Liu, Ming; Gao, Ya; Yuan, Yuan; Yang, Kelu; Shi, Shuzhen; Zhang, Junhua; Tian, Jinhui (Pharmacological research, 2020)
[Display omitted] Corona virus disease (COVID-19) has now spread to all parts of the world and almost all countries are battling against it. This study aimed to assess the efficacy and safety of Integrated Traditional Chinese and Western Medicine (Hereinafter referred to as “Integrated Medicine”) to COVID-19. We searched six major Chinese and English databases to identify randomized controlled trials (RCTs) and case-control studies (CCSs) of Integrated Medicine on COVID-19. Two reviewers independently screened, identified studies, and extracted data. Cochrane Risk of Bias tool and the Newcastle-Ottawa Scale were used to assess the quality of included RCTs and CCSs, respectively. Stata (version 13.0; StataCorp) was used to perform meta-analyses with the random-effects model. Risk ratio (RR) was used for dichotomous data while the weighted mean difference (WMD) was adopted for continuous variables as effect size, both of which were demonstrated in effect size and 95% confidence intervals (CI). A total of 11 studies were included. Four were RCTs and seven were CCSs. The sample size of including studies ranged from 42 to 200 (total 982). The traditional Chinese medicine included Chinese medicine compound drugs (QingFei TouXie FuZhengFang) and Chinese patent medicine (e.g. Shufeng Jiedu Capsule, Lianhua Qingwen granules). Compared with the control group, the overall response rate [RR = 1.230, 95%CI (1.113, 1.359), P = 0.000], cure rate [RR = 1.604, 95%CI (1.181, 2.177), P = 0.002], severity illness rate [RR = 0.350, 95%CI (0.154, 0.792), P = 0.012], and hospital stay [WMD = -1.991, 95%CI (-3.278, -0.703), P = 0.002] of the intervention group were better. In addition, Integrated Medicine can improve the disappearance rate of fever, cough, expectoration, fatigue, chest tightness and anorexia and reduce patients’ fever, and fatigue time (P < 0.05). This review found that Integrated Medicine had better effects and did not increase adverse drug reactions for COVID-19. More high-quality RCTs are needed in the future.